Mint Oil, ɤ-Tocopherol, and Whole Yeast Cell in Sow Diets Enhance Offspring Performance in the Postweaning Period - Hernandez, Lily P.; Dunn, James L.; Wenninghoff, Joel; Hesse, Amanda; Levesque, Crystal L. (Frontiers in Veterinary Science, 2021)
Times of high metabolic activity in gestation and lactation, with periods of stress at weaning, can lead to significant oxidative stress in dam and offspring during suckling and post-weaning. Oxidative stress, an imbalance between pro-oxidant molecules and the antioxidant defense system, negatively impacts growth or reproductive performance. This research's objective was to evaluate the effectiveness of whole yeast cell, peppermint oil, and ɣ-tocopherol in gestation and lactation on maternal oxidative status and offspring growth from birth to market. In study 1, 45 sows and gilts were assigned to 4 diets [Control (CON), control+whole yeast cell (YC), control+mint oil (MO), and control+yeast cell and mint oil (YCMO)] from d110 of gestation through to weaning. 481 weaned offspring were randomly allotted to pens balanced by weight and litter within maternal treatment and received the same diet as the sow for 35d post-wean. In study 2, 53 females were allotted to 4 diets similar to study 1 [CON, YC, MO, and control+ɣ-tocopherol (GT)] from d5 post-breeding to weaning. 605 weaned piglets were randomly allotted to pens within maternal treatment and fed a standard diet for 126d post-wean. Maternal treatment did not impact sow BW and piglet birth weight in either study. YC piglets were heavier (P<0.05) at weaning than CON. In the post-wean period, overall daily gain was greater (P<0.05) for CON than YCMO, with feed intake greater for YCMO than MO, resulting in lower G:F for YCMO-fed pigs. Milk glutathione content tended to be lower (P<0.10) in MO sows than YCMO. In study 2, GT piglets tended to be heavier (P<0.10) at weaning than YC. Lightweight MO and GT pigs were heavier at d42 (P<0.05) than CON and YC. Lightweight MO pigs gained more (P<0.05) during the finishing period than other groups. Colostrum, d4, and 14 milk glutathione content did not differ by treatment. Superoxide dismutase activity in sow sera, colostrum, and milk did not differ in either study. Whole yeast cell and ɣ-tocopherol supplementation in sow lactation diets resulted in heavier offspring. However, pre and postnatal exposure to mint oil benefited light-weight pigs up to market weight.